Critical edition of texts: analyzing the editions of Toá by César Uribe Piedrahita - Carvajal Córdoba, Edwin; Taborda Sánchez, Juan Fernando (Íkala, Revista de Lenguaje y Cultura, 2013)
This text presents the philological analysis of the different editions of the novel Toá:Narraciones de Caucherías (1933) by Colombian writer César Uribe Piedrahita. This analysis is essentially based on the theory of textual criticism, which presents a derivation of a philological methodology for the execution of the critical edition of the text, which implies an edition faithful to the original or closer to the will of the writer. In this way, the analysis of the editions of Toá allowed the identification and selection of them, the exposition of their editorial characteristics and the execution of the comparison from the first edition, and then continuing with the process of textual fixation; process that finally allowed the execution of the critical edition of the novel with their respective philological variants and explanatory notes. Lastly, it is concluded that the editorial process of the five editions of the novel Toá showed inconsistencies of all kinds, inconsistencies that this critical edition aims to correct.